(untitled) (Nigerian Journal of Technology, 2003)
The paper considers the storage of 1000 kg of oranges at a temperature conservation of 1oC with a requirement of 85% to 90% and air circulation velocity of’ 0.3 m/s in the Ware house. Based on the temperature of utilisation, the paper discusses the physiro-chemical problems inherent with a phase change material for a desired cyclic performance and gives the thermo-physical properties of NaF/N2O eutectic mixture used for the analysis. Using the optimal solar radiation for Nsukka (0.9898 KW/m2) the paper shows the calculations of the heat requirements and the surface area of the collector/generator. The paper discusses the design parameters of the components of the aqua-ammonia absorption system. The specification of the ware house based on calculations is also discussed. A model for the simulation of heat transfer phenomenon during storage processes is presented. The paper demonstrates therefore the possibility of the storage in rural areas of Nigeria of perishable agricultural products at different conservation temperatures corresponding to the solidification temperatures of phase change materials using cheap and abundant source of energy.